Design of a water antenna - Lim, Edmond Guo Wei (2017)
Antenna transmission has been crucial in the wireless communication network, although the conventional metal antenna has been mostly used in applications, there is an increase demand for water antennas recently. Advantages such as its ease of reconfigurability, transparency, economical and compactness, water antenna has grown into an interesting topic. However, the efficiency of the water antenna is a major consideration for high gain antenna. In this report, the design of a sea water Yagi antenna is explained. The 3D model was built using the ANSYS High Frequency Structure Simulator (HFSS) software with simulations to illustrate the characteristics of the antenna. Furthermore, the antenna’s radiation performance is verified based on the simulated reflection coefficient, gain, directivity and radiation pattern. In most cases, the objectives of this report were met. However, recommendations are still outlined in this report for future studies. The future work can be divided into improvements in structure of the antenna and type of monopole that can be reintegrated.